EARLY DETECTION SCALE OF RADICALISM IN PESANTREN - Setyawan, M. Adin (Nathiqiyyah, 2024)
The number of radical Islamic boarding schools varies greatly depending on which institution is mentioned. This fact is because the standards used between institutions are different. It is important to be careful with labeling Islamic boarding schools as radical, but recklessly accusing Islamic boarding schools of being radical Islamic boarding schools is also dangerous. This research aims to create a valid and reliable radical Islamic boarding school scale so as to create a quality measuring tool. The creation of the scale began by determining indicators for radical Islamic boarding schools with input from representatives of the leadership of the Ministry of Religion, Muhammadiyah and Nahdhatul Ulama social organizations in Pekalongan Regency. The resulting radical Islamic boarding school scale is valid and reliable. Tests at Salafi Islamic boarding schools in Jogja did not show any signs of radicalism as labeled, there was only one high indicator, namely rejection of state ceremonials.